Identification and Prioritization of Food Insecurity and Vulnerability Indices in Iran - Mohammad Hassan Abolhassani; Fariba Kolahdooz; Reza Majdzadeh; Mohammadreza Eshraghian; Mahboubeh Shaneshin; Se Lim Jang; Abolghasem Djazayery (Tehran University of Medical Sciences, 2015)
Background: Food security is a multi-dimensional phenomenon. The objective of this study was to identify and prioritize major indices for determining food insecurity in Iran. Methods: Descriptive study using the Delphi method was conducted through an email-delivered questionnaire. Fortythree senior experts at national or provincial level were selected based on their work experience and educational background through study panel consultation and snowballing from Tehran and other cities of Iran. During two rounds of Delphi, participants were asked to identify priority indicators for food security at provincial level in Iran. Results: Sixty five percent of Delphi panel participated in the first round and eighty-nine percent of them participated in the second round of Delphi. Initially, 243 indices were identified through review of literature; after excluding indictors, which was not available or measurable at provincial level in Iran, 103 indictors remained. The results of study showed that experts identified "percentage of individuals receiving less than 70% of daily energy requirement" with a median score of 90, as the most influential index for determining food insecurity. "Food expenses as a proportion of the overall expenses of the family", "per capita of dietary energy supply", and "provision of micro-nutrient supply requirement per capita" with median of 80 were in the second rank of food security priority indicators. Conclusion: Out of 243 identified indicators for food security, 38 indicators were selected as the most priority indicators for food security at provincial level in Iran.